Metabolic rearrangements and intratumoral heterogeneity for immune response in hepatocellular carcinoma - Xu, Fei-Qi; Dong, Meng-Meng; Wang, Zhi-Fei; Cao, Li-Dong (Frontiers in Immunology, 2023)
Liver cancer, one of the commonest malignant tumors globally, leads to imperceptible diagnosis accompanied by few treatments and poor prognosis. Hepatocellular carcinoma (HCC) is the most common type of all liver cancer cases. Aggressive cancer cells like HCC experience extensive metabolic rewiring since tumorigenesis, the unique feature ultimately adapts to the neoplastic microenvironment. Intra-tumoral heterogeneity (ITH) in cancer defines the distinct genetic features and different phenotypes in the same tumoral region. As one of the most unique properties of malignant cancers, ITH renders tumor differences in many aspects including but not limited to growth, and chemotherapy resistance, which partly leads to metabolic reprogramming. Moreover, the different metabolic phenotypes might also cause different resistance to chemo/radio-therapy. In this review, we summarize metabolic reprogramming of glucose and tumoral heterogeneity and their associations in hepatocellular carcinoma for a better understanding of the mechanisms of HCC oncogenesis.